Pendidikan Kesehatan dalam Kelas Balita dan Pembuatan Makanan Pendamping ASI (MP ASI) di Posyandu Puskesmas Buaran Kota Pekalongan - Andanawarih, Putri; Ulya, Ni'matul; Artanti, Swasti (Jurnal ABDIMAS-HIP Pengabdian Kepada Masyarakat, 2024)
Children under five are one of the populations most at risk of experiencing various health problems (illness) and death. The most common problem related to fulfilling toddler nutrition is lack of protein energy. The classification of toddlers includes: stunting (short body), thinness, and malnutrition. Poor nutritional conditions in toddlers can also cause child death. Approximately 45 (%) deaths among children under five are related to malnutrition. The aim of this activity is to provide benefits and make it easier for mothers of toddlers in choosing and giving MP-ASI to babies and toddlers. This activity uses the following methods: (a) Counseling about Mother Toddler Classes, (b) Counseling about the benefits of MP-ASI for toddlers, (c) Counseling about choosing a healthy MP-ASI menu, (d) Discussion and questions and answers. The results of the health education that has been carried out show an increase in the knowledge of mothers with toddlers about how to care for toddlers and make good complementary foods for breast milk with post test scores of 18 participants having good knowledge.